Validation of Rapid Interactive Screening Test for Autism in Toddlers Using Autism Diagnostic Observation Schedule™ Second Edition in Children at High-Risk for Autism Spectrum Disorder - Kong, Xue-Jun; Sherman, Hannah Tayla; Tian, Ruiyi; Koh, Madelyn; Liu, Siyu; Li, Alice Chukun; Stone, William S. (Frontiers in Psychiatry, 2021)
The Rapid Interactive screening Test for Autism in Toddlers (RITA-T) is a fast and inexpensive early screening measure for autism spectrum disorder (ASD) that was tested previously in children 18–36 months-old; the current validation study compared the RITA-T with the Autism Diagnostic Observation Schedule™ Second Edition (ADOS-2). The hypothesis is to validate the RITA-T with comparison to the ADOS-2. Thirty-five individuals (18–84 months-old) identified as at risk for ASD received the RITA-T and the ADOS-2 during a single visit. Participants were split into two age groups and both whole-group and sub-group data analysis were conducted. With all participants, RITA-T scores correlated significantly with ADOS-2 total scores (P < 0.001), social affect (SA) sub-scores (P < 0.001), and restrictive and repetitive behavior (RRB) sub-scores (P < 0.05). Similarly, ADOS-2 total and SA scores were significantly correlated in both age groups, while the RRB sub-score was only significant in females (P < 0.05). Lastly, correlations using subgroups based on ethnicity were only significant in the minority (“Other”) group for ADOS-2 total scores and in the Asian group for SA sub-scores (P < 0.05). Our receiver operating characteristic analysis showed that the optimal cut-off score of the RITA-T was consistently at 14, with a sensitivity of 81% and a specificity of 89% in the combined age group with the ADOS-2 and with a sensitivity 74% and specificity 50% with the DSM-5; The area under the curve was 0.84 (95%CI: 0.69–0.99) for ASD classified by ADOS-2 and 0.89 (95%CI: 0.79–0.99) for ASD diagnosed by DSM-5. The RITA-T performed similarly to the ADOS-2 when both were administered in a single visit. Significant correlations between the measures help validate the potential usefulness of the RITA-T as a rapid early screening measure of ASD. This study helps to show that the RITA-T may be used in a larger age range than originally reported and in different ethnic groups. The study involves human participants and was reviewed and approved by the Institutional Review Board (IRB) of Massachusetts General Hospital (MGH, 2017P0000857).